Degrowth and Direct Democracy: A Discourse Network Analysis of Swiss Parliament - Grolimund,Nils (2025)
This thesis serves as a first inquiry into studying discourse coalitions in the Swiss Parliament in a degrowth-related context. Through the use of Argumentative Discourse Analysis and Discourse Network Analysis, I investigate the parliamentary dynamics in the context of degrowth-related popular initiatives. By examining how four storylines shape the discourse, this research aims to find discourse coalitions that emerge within the Swiss Parliament as well as potential partners for degrowth proponents. The findings highlight the complex interplay between different parliamentary groups and their respective perspectives on degrowth-related themes, which sheds light on the challenges and opportunities of implementing degrowth policies through parliamentary means. While the case-by- case findings differ from each other, there exist broad left-right discourse coalitions. This research contributes to degrowth research in the Swiss context and at large by shedding light on the policy-making process and potential avenues for degrowth proponents.
Keywords: Switzerland; degrowth; discourse network analysis; storylines; parliamentary politics